Hormonal Study of the different phenotypes of polycystic ovary syndrome (Journal of the College of Basic Education, 2022)
This study was done in Kamal al-Samarrai hospital/ Baghdad since the beginning of July2013till December, 2013. Hormonal changes in the serum of polycystic ovary syndrome (PCOS) infertile women and control women were estimated in the second day of the menstrual cycle. Fifty females with PCOS (25 severe, 25 mild) were included in this study in addition to 25 apparently healthy females as a control group. This study aim to evaluate and compare hormonal changes between the different PCOS phenotypes to those in healthy women. LH, LH/FSH ratio and testosterone concentrations was high in severe PCOS than in the mild PCOS and control group (P<0.05). Similarly, compared with control group LH, LH/FSH ratio and testosterone level were also elevated in women with mild PCOS (P<0.05), while there were no differences in FSH level between the two phenotypes of PCOS and controls (P>0.05). In conclusion hormonal imbalance plays an important role in PCOS, as found milder form of hormonal imbalance in mild phenotype of PCOS.